Graphic design : Australian style manual - Barnum, Andrew Townley (McGraw Hill, 2012)
The theory and thought behind graphic design in an Australian and New Zealand context is covered, giving students and professionals the knowledge, tools and inspiration to channel their creativity into professional practice